2004
DOI: 10.1152/physiolgenomics.00104.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes associated with fibronectin-induced cardiac myocyte hypertrophy

Abstract: (FN) is an extracellular matrix protein that binds to integrin receptors and couples cardiac myocytes to the basal lamina. Cardiac FN expression is elevated in models of pressure overload, and FN causes cultured cardiac myocytes to hypertrophy by a mechanism that has not been characterized in detail. In this study, we analyzed the gene expression changes induced by FN in purified rat neonatal ventricular myocytes using the Affymetrix RAE230A microarray, to understand how FN affects gene expression in cardiac m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…27,28 Clustered with Akt and gp130 was fibroblast growth factor-1, an angiogenic growth factor that has earlier been shown in human cardiac hypertrophy 29 and that may reflect that blood vessel recruitment is an important feature of normal tissue growth. 30 An increase in connective tissue growth factor (CTGF) expression was seen in late LVH, similar to findings in other models of cardiac hypertrophy, 31 and its well-characterized profibrotic effect, including its ability to induce cardiac fibroblast proliferation and also extracellular matrix expansion. 32 Hayata et al 33 have shown that cardiac myocytes stimulated with CTGF and its C-terminalregion peptide showed an increase in the cell surface area.…”
Section: Proliferation/cell Growthsupporting
confidence: 73%
“…27,28 Clustered with Akt and gp130 was fibroblast growth factor-1, an angiogenic growth factor that has earlier been shown in human cardiac hypertrophy 29 and that may reflect that blood vessel recruitment is an important feature of normal tissue growth. 30 An increase in connective tissue growth factor (CTGF) expression was seen in late LVH, similar to findings in other models of cardiac hypertrophy, 31 and its well-characterized profibrotic effect, including its ability to induce cardiac fibroblast proliferation and also extracellular matrix expansion. 32 Hayata et al 33 have shown that cardiac myocytes stimulated with CTGF and its C-terminalregion peptide showed an increase in the cell surface area.…”
Section: Proliferation/cell Growthsupporting
confidence: 73%
“…Ventricular myocytes were isolated from 1-or 2-dayold newborn Sprague-Dawley rats according to an established protocol 26,30 and in compliance with the 'Guiding Principles for the Care and Use of Animals.' In brief, ventricles were digested with trypsin and DNAse I and nonmyocytes were removed by preplating in uncoated tissue culture dishes for 1 h. Nonattached cardiac myocytes were plated in tissue culture dishes that were precoated with 0.5 mg/cm 2 of FN (Sigma, St Louis, MO, USA) or with 100 mg/cm 2 of gelatin for 3-4 h. Cells were usually plated at a density of 500 cells/mm 2 and cultured for 24 h in MEM containing 5% bovine calf serum and 0.1 mM bromodeoxyuridine at 371C in 1% CO 2 .…”
Section: Isolation and Culture Of Nrvmmentioning
confidence: 99%
“…26 Briefly, cardiac myocytes were cultured in eight-well slides, fixed in PBS containing 2% paraformaldeyde, permeabilized with 0.1% Triton X-100, and stained with primary and secondary antibodies diluted in PBS containing 0.1% Tween 20 (PBS-T) and 5% normal donkey serum. Pimary antibodies included rabbit anti-atrial natriuretic peptide (ANP, Peninsula Laboratories, Belmont, CA, USA), mouse clone 65.1 anti-ILK, anti-PARVA antibody 3B5, and anti-sarcomeric actinin antibody (Sigma #A7811).…”
Section: Immunofluorescencementioning
confidence: 99%
See 2 more Smart Citations